The economic consequences of the Doha Round for Ireland - Matthews, Alan; Walsh, Keith (Economic & Social Studies, 2006)
This paper provides a quantitative study of the economic effects of a stylised simulation of trade liberalisation for Ireland using the GTAP model. The experiment incorporates the liberalisation of agricultural, manufacturing and services trade as well as measures to improve trade facilitation. The simulation is implemented against a baseline projection of the Irish and world economy over the next decade. Overall, Ireland?s welfare will increase as a result of further trade liberalisation, with particularly strong gains from services liberalisation. The industrial liberalisation scenario also generates positive gains to Ireland, while agricultural liberalisation has a slightly negative effect on the overall economy.
Keywords: Quantitative economics; Trade liberalisation; Doha Round; Ireland; World trade; Agricultural liberalisation